(untitled) (Journal of the College of Education for Women, 2018)
The aim of the study is to investigate the extent to which the teachers of Islamic education and their teachers taught the technological innovations in the universities and to test the significance of the differences between the averages of the degree of practice according to the variables: gender, experience, scientific qualification, and educational stage. To achieve these objectives, a questionnaire consisting of (20) (20) teacher and school, teachers of Islamic education in Iraqi universities. The results indicated that the degree of the practice of Islamic education teachers and their teachers of technological innovations was moderate, and there were statistically significant differences in the variable of scientific qualification in favor of higher scientific qualification. There were no significant differences between the average of the practice of the gender variable and the educational stage. The study recommends training teachers of Islamic education and their teachers to employ technological innovations in learning, during the teaching process, and to provide study climates that facilitate the application of technological innovations in classrooms.